2012
DOI: 10.1371/journal.pone.0032459
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Kinase Promotes Acquisition of Stem Cell-Like Properties: A Potential Therapeutic Target in Head and Neck Squamous Cell Carcinoma Stem Cells

Abstract: Members of the EGFR/ErbB family of tyrosine kinases are found to be highly expressed and deregulated in many cancers, including head and neck squamous cell carcinoma (HNSCC). The ErbB family, including EGFR, has been demonstrated to play key roles in metastasis, tumorigenesis, cell proliferation, and drug resistance. Recently, these characteristics have been linked to a small subpopulation of cells classified as cancer stem cells (CSCs) which are believed to be responsible for tumor initiation and maintenance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 25 publications
6
61
0
Order By: Relevance
“…Interaction of these surface receptors can cause proliferation, chemotherapy resistance and invasion in HNSCC cell lines (27,28). EGFR also increases CD44 mRNA expression (29). Additionally, proliferating tumor cells (Ki-67) are often CD44 + .…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of these surface receptors can cause proliferation, chemotherapy resistance and invasion in HNSCC cell lines (27,28). EGFR also increases CD44 mRNA expression (29). Additionally, proliferating tumor cells (Ki-67) are often CD44 + .…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence from previous studies have shown that CD44 could activate Rho family members to initiate intracellular signaling pathways and RhoA was involved in the regulation of YAP phosphorylation [26,[29][30][31][32][33]. Thus, we speculated that CD44 might act through RhoA signaling to regulate YAP expression.…”
Section: Rhoa Is Involved In the Regulation Of Cd44 On Yap Expressionmentioning
confidence: 92%
“…CD44 plays important roles in tumor cell apoptosis, proliferation and migration [29][30][31]. Recent researches also indicated that YAP might have a similar function to CD44 [12,13].…”
Section: Cd44 and Yap Modulate The Cancer Cell Apoptosis Proliferatimentioning
confidence: 99%
“…In addition to their role in junction formation and stabilization, polarity proteins also impact cellular proliferation and their loss can block apoptosis, when in conjunction with oncogenes, can significantly increase tumor growth and invasion [48]. Of note, increased TAZ has been shown to activate the EGFR pathway, which can then result in a loss of E-cadherin expression at adherence junctions, drive migration, increase CD44 expression, and promote growth in soft agar and mammospheres [30,31,36]. It is interesting to note that loss of Llgl1 results in a downregulation of E-cadherin, as well as cell migratory behavior indicative of a loss of cell-cell junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics that define these cells include serial transplantation in vitro and in vivo, and the expression of a variety of surface markers, including CD44 hi /CD24 lo , CD44 hi , and CD49f lo , among others [25][26][27][28][29]. Of note, TAZ nuclear translocation is known to potentiate EGFR signaling pathways, which in turn can increase CD44 transcription and stem cell characteristics [30,31]. Due to the connection between receptor localization within a cell and its ability to activate these pathways, an epithelial population may possess a plasticity depending upon their state of polarity.…”
Section: Introductionmentioning
confidence: 99%